Analysis of the Constitutional Court’s the Judge's Decision Ratio in Interpreting the Meaning of Riots (in Constitutional Court Decision No. 115/PUU-XXII/2024) - Ahmad Saifuddin (CV Edujavare Publishing, 2026)
This study examines Constitutional Court Decision Number 115/PUU-XXII/2024 regarding the interpretation of the term